The rewrite process in haiku the Flora Thomé - Angela Gumieiro (ArReDia, 2015)
Aware of the diversity in poetry, Flora Thomé is dedicated to oriental poetic composition and becomes, in Mato Grosso do Sul, the main disclosing this poetry of Japanese origin. Display in some compositions of Haiku, 1999 book, the resumption of verses belonging to poems previously produced in Portraits, 1993. This text presents a study of the poems that make up the works of Flora Thomé: Haiku, 1999 and Portraits, published in 1993 by establishing a dialogue between them, with respect to the rewriting process, as literary device employed in the poetics of the author.